2020
DOI: 10.3390/sym13010052
|View full text |Cite
|
Sign up to set email alerts
|

Study on Fault Diagnosis Method of Planetary Gearbox Based on Turn Domain Resampling and Variable Multi-Scale Morphological Filtering

Abstract: The turn domain resampling (TDR) method is proposed in the paper on the basis of the existing angle domain resampling for solving the problem of non-fixed fault frequency under variable working conditions. TDR can select the appropriate sampling order according to the influence of frequency conversion, which avoided the error caused by the spline interpolation method. It can provide accurate parameters for the subsequent calculation of the equivalent frequency order. Variable multi-scale morphological filterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…. The expansion operator eliminates the positive pulse, and the negative pulse is sharper, while the corrosion operator eliminates the negative pulse, and the positive pulse is sharper [11] .…”
Section: Mathematical Morphological Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…. The expansion operator eliminates the positive pulse, and the negative pulse is sharper, while the corrosion operator eliminates the negative pulse, and the positive pulse is sharper [11] .…”
Section: Mathematical Morphological Algorithmmentioning
confidence: 99%
“…(1) The experimental signal is variable speed signal, and the traditional fault feature extracted method will produce frequency ambiguity. In order to solve this problem, the paper first applied the Turn Domain Resampling (TDR) proposed by our group [11] to (2) The VMSMD proposed in this paper is used to de-noise the four groups of signals with different fault types after resampling, and then the envelope demodulation of the resampling signal is carried out. The processing results are shown in Fig.…”
Section: Experimental Signal Analysis Of Planetary Gearbox Sun Wheel Failurementioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the adaptive MMF is effective in extracting fault features. Liu et al proposed a variable multi-scale MMF method to filter resampling signals and obtain signals with less noise for feature extraction [55]. They used the Chebyshev window function as SE and opening-closing and closingopening mean as the morphological operator.…”
Section: Structural Elementmentioning
confidence: 99%
“…(1) The experimental signal is variable speed signal, and the traditional fault feature extracted method will produce frequency ambiguity. In order to solve this problem, the paper first applied the Turn Domain Resampling (TDR) proposed by our group [11] to equivalently transform the signals with variable speed to the four health status signals collected. The original time domain signals and the resampled signals are shown in Fig.…”
Section: Experimental Signal Analysis Of Planetary Gearbox Sun Wheel Failurementioning
confidence: 99%